Thermodynamic modeling of inhibitors’ role in preventing from gas hydrate formation in the pipelines - Kakavand, Fateme Sadat Mosavi (2015)
The existence of water beside gas has led to the creation of gas hydrate formation phenomenon in these pipelines. The phenomenon causes to basic financial and operational problems in the system. For this reason, the flow purpose of the present study was to simulate the formation condition in a specific flow and thermodynamic conditions and finally to provide the best possible solution to this problem. The Van Der Waals & Plague equation was used to thermodynamic modeling in the terms of temperature and pressure and the computer coding was carried out by MATLAB software. In addition, the results of Green & Perry study were used to utilize from physical characteristics, such as critical temperature, critical pressure, acentric factor and the temperature of quadruple points of elements forming hydrate .the results of this study indicated that increasing the concentration of inhibitor in system at the specified temperature, delay the hydrate formation. Moreover, temperature rising can also increase the effect of solvents. Therefore, two parameters of ambient temperatures in hot seasons or using heaters for pipelines can reduce the risk to a minimum in critical (sensitive) points. Finally, the used model in this design which has had some changes in variables properly can see the needs and meanwhile it is usable for other similar changes by a brief change.